Recombinant Phage Coated 1D Al2O3 Nanostructures for Controlling the Adhesion and Proliferation of Endothelial Cells - Lee, Juseok; Jeon, Hojeong; Haidar, Ayman; Abdul-Khaliq, Hashim; Veith, Michael; Aktas, Cenk; Kim, Youngjun (Hindawi Publishing Corporation, 2015)
A novel synthesis of a nanostructured cell adhesive surface is investigated for future stent developments. One-dimensional (1D) Al2O3 nanostructures were prepared by chemical vapor deposition of a single source precursor. Afterwards, recombinant filamentous bacteriophages which display a short binding motif with a cell adhesive peptide (RGD) on p3 and p8 proteins were immobilized on these 1D Al2O3 nanostructures by a simple dip-coating process to study the cellular response of human endothelial EA hy.926. While the cell density decreased on as-deposited 1D Al2O3 nanostructures, we observed enhanced cell proliferation and cell-cell interaction on recombinant phage overcoated 1D Al2O3 nanostructures. The recombinant phage overcoating also supports an isotropic cell spreading rather than elongated cell morphology as we observed on as-deposited Al2O3 1D nanostructures.